Biocatalysis in Spain: A field of success and innovation. Issue 3 (4th May 2018) - Alcántara, Andrés R.; García-Junceda, Eduardo; Gotor, Vicente; Plou, Francisco J.
Abstract: This is the presentation of the Special Issue "Biocatalysis in Spain", covering the work of several Spanish groups in the field of Biocatalysis and Biotransformations. Thus, both research articles and reviews allow one to draw an accurate view of the state-of-the-art development in Spain.